Outcomes in children of women with type 2 diabetes exposed to metformin versus placebo during pregnancy (MiTy Kids): a 24-month follow-up of the MiTy randomised controlled trial. Issue 3 (March 2023) - Feig, Denice S; Sanchez, J Johanna; Murphy, Kellie E; Asztalos, Elizabeth; Zinman, Bernard; Simmons, David; Haqq, Andrea M; Fantus, I George; Lipscombe, Lorraine; Armson, Anthony; Barrett, Jon; Donovan, Lois; et al.
Summary: Background: Metformin is increasingly being used during pregnancy, with potentially adverse long-term effects on children. We aimed to examine adiposity in children of women with type 2 diabetes from the Metformin in Women with Type 2 Diabetes in Pregnancy (MiTy) trial, with and without in-utero exposure to metformin, up to 24 months of age. Methods: MiTy Kids is a follow-up study that included infants of women who participated in the MiTy randomised controlled trial, receiving either oral 1000 mg metformin twice daily or placebo. Caregivers and researchers remained masked to the type of medication (metformin or placebo) mothers received during their pregnancy. Anthropometric measurements, including weight, height, and skinfold thicknesses, were taken at 3, 6, 12, 18, and 24 months. At 24 months, linear regression was used to compare the BMI Z score and sum of skinfolds in the metformin versus placebo groups, adjusted for confounders. Fractional polynomials were used to assess growth trajectories. This study is registered with ClinicalTrials.gov, NCT01832181 . Findings: Of the 465 eligible children, 283 (61%) were included from 19 centres in Canada and Australia. At 24 months, there was no difference between groups in mean BMI Z score (0·84 [SD 1·52] with metformin vs 0·91 [1·38] with placebo; mean difference 0·07 [95% CI –0·31 to 0·45], p=0·72) or mean sum of skinfolds (23·0 mm [5·2] vs 23·8 mm [5·4]; mean difference 0·8 mm [–0·7 to 2·3], p=0·31). Metformin was not a predictor of BMI Z score at 24 months of age (mean difference –0·01 [95% CI –0·42 to 0·37], p=0·92). There was no overall difference in BMI trajectory but, in males, trajectories were significantly different by treatment (p=0·048); BMI in the metformin group was higher between 6 and 24 months. Children of women with type 2 diabetes were approximately 1 SD heavier than the WHO reference population. Interpretation: Anthropometrics were similar in children exposed and those not exposed to metformin in utero; hence, overall, data are reassuring with regard to the use of metformin during pregnancy in women with type 2 diabetes and the long-term health of their children. Funding: Canadian Institute for Health Research.